Pulmonary resection for isolated pulmonary metastasis: patterns of disease - Nichkaode, Prabhat Bhaskarrao; Parakh, Aditya; Sharma, Anurag (International Surgery Journal, 2017)
Background: Pulmonary metastasectomy dates back to 1880s, sub lobar resections, lobectomy and pneumonectomy, described in the setting of metastatic sarcoma, renal cell cancer, testicular NSGCT. Extremity sarcoma is the most common primary site for metastasis to lung. Almost 20 % of patients with extremity sarcoma, give rise to isolated pulmonary metastasis at some point in the course of the disease. Though pulmonary metastasis commonly arises from primary tumors in extremities, they may arise from any histologic variant. Despite progresses in multimodality treatment, there are significant deaths, after metastasis from soft tissue malignancies. There is evidence that surgical resection is the treatment of choice for isolated pulmonary metastasis from extremity sarcoma. Chemotherapy has proved to be ineffective to increase survival in such cases. Keeping this in mind we report an analysis of 11 such cases in terms of patterns of disease, for Isolated pulmonary metastasis originating from various histologic variants. Methods: This is a retrospective study from July 2006 to September 2016, carried out at NKP Salve Institute of Medical Sciences. During this period, total 13 patients were admitted with Isolated pulmonary metastasis. Out of 13 patients 2 patients were later on proved to have metastasis in the liver and so excluded from study. Of 11 patients, metastasis from soft tissue sarcoma of extremity were (5), cancer of uterine cervix (3), non seminomatous germ cell tumor of testis (3). All 11 patients were treated with pulmonary resectional surgery. Patterns of disease in terms of specific survival from various histological variants. Results: The median survival for soft tissue sarcoma from the diagnosis of pulmonary metastasis for all 5 patients was 18 to 26 months. Reports suggest, with non-operative therapy for soft tissue sarcoma, the median survival was 11 months. After pulmonary mastectomy, three-year survival for these patients was around 23%. For world wide data suggest the prevalence of pulmonary metastasectomy was 3.6% in cancer cervix. In the present study, the mean disease-free duration for cancer cervix after pulmonary resection was more than 60 months. In the present study, all 3 patients are still alive even after 5 years with no recurring disease. Reports published in 2016 surgical clinics show 5-year survival in 80%. Patients with NSGCT showed persistent rising levels of (ß HCG, æ fetoprotein, LDH) and CT evidence of active pulmonary metastasis, with 4 or less nodules were subjected for surgery, with outcome of 2 patients had recurrent disease died at the end of 27th month. 1 patient is still alive after 11 years. Patients with complete resection of all metastatic disease was the important prognostic factor for survival. Conclusions: Isolated pulmonary metastasis is not a very common disease in this part of the world. Complete surgical resection of metastasis is the single most important factor which determines outcome in these patients. Disease free interval (DFI), number of metastatic nodules, are important factors in surgical decision making. Long term survival is possible in selected patients, even when recurrent disease is resected.